Impact of Acipimox Therapy on Free Fatty Acid Efflux and Endothelial Function in the Metabolic Syndrome: A Randomized Trial. Issue 11 (1st October 2019) - Aday, Aaron W.; Goldfine, Allison B.; Gregory, Justin M.; Beckman, Joshua A.
Abstract : Objective: Insulin resistance is associated with increased lipolysis and elevated concentrations of free fatty acids (FFA), which in turn contribute to impaired vascular function. It was hypothesized that lowering FFA with acipimox, a nicotinic acid derivative that impairs FFA efflux, would improve endothelial function, measured by flow‐mediated dilation (FMD), in individuals with metabolic syndrome. Methods: A total of 18 participants with metabolic syndrome and 17 healthy controls were enrolled and treated with acipimox 250 mg orally every 6 hours or placebo for 7 days in a randomized, double‐blind, crossover trial. Results: Acipimox reduced FFA concentrations among individuals with metabolic syndrome to near normal levels ( P = 0.01), but there was no change among healthy controls ( P = 0.17). Acipimox did not improve endothelial‐dependent FMD in either group (metabolic syndrome: P = 0.42; healthy controls: P = 0.16), although endothelial‐independent nitroglycerin‐mediated dilation among those with metabolic syndrome tended to increase (20.3%, P = 0.06). There were no changes in blood lipids or markers of inflammation following therapy. There was minimal correlation between change in FMD and baseline measures of BMI ( ρ = −0.09) or waist circumference ( ρ = −0.15). Conclusions: In groups with normal or elevated baseline FFA, short‐term reductions do not improve endothelial function assessed by FMD.